English and the Indian short story : essays in criticism - Ramanan, Mohan, 1949-; Sailaja, P. (Pingali), 1962-; National Seminar on "English and the Indian Short Story" (1994 : Dept. of English, University of Hyderabad) (New Delhi : Orient Longman Ltd., 2000)
Contributed articles presented at the National Seminar on "English and the Indian Short Story" held in August 1994 at the Dept. of English, University of Hyderabad.
Includes bibliographical references.
Keywords: Short stories, Indic (English) -- History and criticism -- Congresses; Indic fiction (English) -- 20th century -- History and criticism -- Congresses